HUBUNGAN MINAT BELAJAR, KECERDASAN EMOSIONAL DAN NILAI UAS ALAT UKUR TERHADAP HASIL BELAJAR SISWA SMK DI JOMBANG - Samudra, Agung (Universitas Hasyim Asy'ari, 2019)
The aim of this study was to determine the relationship Learning Interest, Emotional Intelligence and FinalExam Scores Measuring Devices Competency Standard Describes the Processesing of Energy ConversionEngineering Against the Students’ Learning Outcomes of SMK in Jombang.This study used quantitative descriptive approach. This research was a correlation study. The method usedfor data retrieval is using questionnaires and tests. The questionnaire used to determine students' interestsand emotional intelligence. While the test, used to determine student learning outcomes, and documentationto determine the Final exam scores measuring devices of students.Based on the results of data analysis with significance level of 5%, it can be concluded: (1) There is asignificant positive relationship between learning interest with the students’ learning outcomes of SMK inJombang. Learning interest affect student learning outcomes by 21.7%. (2) There is a significant positiverelationship between emotional intelligence with the students’ learning outcomes of SMK in Jombang.Emotional intelligence affect student learning outcomes of 25.9%. (3) There is a significant positiverelationship between the final exam scores measuring devices with the students’ learning outcomes of SMKin Jombang. Final exam scores measuring devices affect student learning outcomes by 23.2%. (4) There is asignificant positive relationship between learning interest , emotional intelligence and final exam scoresmeasuring devices together with the students’ learning outcomes of SMK in Jombang. Learning interest,emotional intelligence and value UAS measuring instrument together affect student learning outcomesamounted to 34.0%. Keywords: learning interest, emotional intelligence, final exam scores measuring devices, learningoutcomes